Web-Based E-LKPD for the Indonesian History Subject for Grade XI Senior High School - Amalini Lutfia Ozila; Zelhendri Zen (Indonesian Journal Of Educational Research and Review, 2023)
Education is currently inseparable from technological developments. The integration of technology into the education field provides renewal in various aspects. One of them is the use of technology in the learning process. The problems found in the Indonesian History subject were the low interest and low learning outcomes of the students. This is due to the great influence of smartphone development. One way to increase the students' understanding and interest in learning history is through an electronic form of LKPD (E-LKPD) displayed via the web. This research aims to analyze the process, validity, practicality and effectiveness of the web-based E-LKPD development for Indonesian History subject for Grade XI Senior High School. This study used the development and research (R&D) method with the ADDIE model. The data analysis technique in this research used a Likert scale 4 questionnaire to determine the validity and practicality of web-based E-LKPD product. For the product effectiveness, a pre-test and post-test were carried out to see the achievement of student learning outcomes. The validity test of the E-LKPD involved material, media and language experts. The practicality test involved two educators of Indonesian history and 71 students from class XI at Senior High School. The results of the validity test from material experts were 3.9, from media experts were 3.8 and from linguists were 3.8 in the very valid category. The results of the practicality test by educators were 3.8 and from students were 3.7 in the very practical category. The gain score results of the effectiveness test through the pre-test and post-test of XI MIPA 7 were 0.9 and XI MIPA 8 were 0.8 in the very high category.